OMEGA-3 POLYUNSATURATED FATTY ACIDS IN ATRIAL FIBRILLATION PREVENTION AFTER SURGICAL MYOCARDIAL REVASCULARIZATION - A. V. Panov; B. A. Tatarskiy; M. L. Gordeev; R. I. Nilk (Рациональная фармакотерапия в кардиологии)
Aim. To estimate an efficacy of therapy with ω-3 polyunsaturated fatty acids (PUFA) in patients with ischemic heart disease (IHD) before and after coronary artery bypass graft (CABG).Material and methods. 189 patients (125 men, 64 women; aged 64,2±9,4 y.o.) with IHD having indications to CABG were enrolled in the study. Patients of the first group (control) had standard pre- and postoperative treatment. Patients of the second group received ω-3 PUFA (ОМАCОR, Solvay Pharma) 2 g/daily in addition to standard therapy. Both groups were similar in clinical characteristics. ω-3 PUFA therapy started 7±4 day before CABG, renewed in early postoperative period (24-36 hours after surgery) and lasted next 14 days. Efficacy of the therapy was estimated by atrial fibrillation frequency in postoperative period and time before hospital discharge after CABG. An automatic complex for transesophageal electrophysiological cardiac examination was used for the estimation of atrial conduction before and after CABG.Results. Omacor therapy in patients with ICD before CABG and in the early postoperative period reduces atrial fibrillation risk. It results in reduction of hemodynamic disorders and time before hospital discharge. Conclusion. Omacor therapy is safe and can be recommended to all patients going through CABG.